2018
DOI: 10.1039/c8nr00677f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the nanofiber chemistry and orientation of biodegradable poly(butylene succinate)-based scaffolds on osteoblast differentiation for bone tissue regeneration

Abstract: Innovative nanofibrous scaffolds have attracted considerable attention in bone tissue engineering, due to their ability to mimic the hierarchical architecture of an extracellular matrix. Aiming at investigating how the polymer chemistry and fiber orientation of electrospun scaffolds (ES) based on poly(butylene succinate) (PBS) and poly(butylene succinate/diglycolate) (P(BS80BDG20)) affect human osteoblast differentiation, uniaxially aligned (a-) and randomly (r-) distributed nanofibers were produced. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…Then, a nanofibrous network is created on the collector, which has been utilized for different tissue engineering applications. 8,9 In the case of piezoelectric polymers, nanofibrous piezoelectric scaffolds can be obtained by controlling the electrospinning parameters. The most studied piezoelectric polymer is poly(vinylidene fluoride) (PVDF) 10 , and its increasing research interest stems from its fascinating properties due to the high electrical dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a nanofibrous network is created on the collector, which has been utilized for different tissue engineering applications. 8,9 In the case of piezoelectric polymers, nanofibrous piezoelectric scaffolds can be obtained by controlling the electrospinning parameters. The most studied piezoelectric polymer is poly(vinylidene fluoride) (PVDF) 10 , and its increasing research interest stems from its fascinating properties due to the high electrical dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It has also been reported that a certain degree of nanofiber alignment is important for specific bio-medical applications. [16][17][18] The combined role of polymer chemical structure and nanofiber alignment shows a significant effect in promoting interactions with cells, such as controlling the phenotype and morphology of osteoblasts 16 and skeletal myoblasts. 14,15,19 In vascular graft applications, topography driven from the size distribution of nanofibers influences the platelets adhesion on membranes and the blood compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were scraped from all the samples, including T, and lysed with ice-cold lysis buffer (1X RIPA buffer containing 1 mM and 1X protease inhibitor (Protease Inhibitor Tablets, SIGMA) for 30 min on ice. The lysates were then used for western blot analysis according literature protocol (Cristofaro et al, 2018). Primary antibodies anti-phosphorylated AKT and anti-AKT (diluted 1:500), anti-ERK and anti-phosphorylated ERK (diluted 1:1000), anti-BAX and anti-BCL-XL (diluted 1:500), anti-β-actin (diluted 1:500) and appropriate secondary antibodies HRP-conjugated were used.…”
Section: Western Blot Analysismentioning
confidence: 99%